NEURO-PSIKOLINGUISTIC APPROACH IN BUIDING STUDENTS’C CHARACTER IN THE PREPUBERTAL AGE: A REFLECTION OF JAPAN’S BASIC EDUCATION SYSTEM - Gusdi Sastra (International Conference on Languages and Arts, 2014)
This paper discusses the implementation of neuro-psycholinguistic in building students’ character in the prepubertal age in primary school. Psycholinguistic approach composed consists of three things, namely: comprehension, production, and bio-neurological. Reflecting the basic education learning system in Japan, it tries to explain how the Japanese government's role in building the students’ character, especially at primary school age. Various competences, cognitive, psychomotor, and affective domain, in prepubertal age are being discussed through neurolinguistic studies how Japan become a advanced country. It was built together by the three pillars to build students’ character, the government, schools, and parents. Based on psycholinguistic approach, it reveals that the Japanese character is built through a long process, especially in the prepubertal age, as this age is the rapid nerve cells in the brain work in the process of localization of various intelligence functions, especially the treatment to the children in the area of emotional intelligence of the right hemisphere of his brain, so it internalized into the character of each individual until adulthood. From the review of the theoretical and practical neuro-psycholinguistic approach to build the students’ character, proving that education plays an important role in the growth and development of children as the future generation. Indonesian language learning competence (especially "writing"  used to be called the "composing" is expected to develop language skills so that students are characterized by 4 basic competencies, i.e. reading, writing, listening, and speaking. Through these basic competencies, it is expected that the students will have core competencies and soft skills such as hardskills that reflects the attitudes, skills, and knowledge students that are interlinked subjects to each student-student in the group. In addition, through the concept of "Liderlis" (see, hear, and write), "Firalis" (think, feel, and write), and "Menudas" (read - write - smart) will produce the students with good character, that are able to translate text and experience into values ​​which will build the personality of the students. It require good cooperation between the government, teachers, and parents together in creating an educated and character of human being in Indonesia.   Keywords:  neurolinguistics, Japan’s character, prepubertal age, writing